2008
DOI: 10.1039/b706023h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure methods for studying surface-enhanced Raman scattering

Abstract: This critical review highlights recent advances in using electronic structure methods to study surface-enhanced Raman scattering. Examples showing how electronic structure methods, in particular time-dependent density functional theory, can be used to gain microscopic insights into the enhancement mechanism are presented (150 references).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
625
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 613 publications
(636 citation statements)
references
References 142 publications
(190 reference statements)
9
625
0
2
Order By: Relevance
“…As Jensen et al [22] suggested, the enhancement factor under off-resonance excitation is a measure of CHEM enhancement, which is due to ground state chemical interactions between the molecule and active substrate. Unlike the charge transfer enhancement, CHEM enhancement is not limited to the resonant or offresonant region because it is not associated with any excitations of the substrate-molecule system.…”
Section: Resultsmentioning
confidence: 99%
“…As Jensen et al [22] suggested, the enhancement factor under off-resonance excitation is a measure of CHEM enhancement, which is due to ground state chemical interactions between the molecule and active substrate. Unlike the charge transfer enhancement, CHEM enhancement is not limited to the resonant or offresonant region because it is not associated with any excitations of the substrate-molecule system.…”
Section: Resultsmentioning
confidence: 99%
“…The Becke-Perdew (BP86) XC-potential [91,92] and a triple-polarized slater type (TZP) basis set from the ADF basis set library were used in our simulation. The validity of using DFT and ADF for quantum mechanical SERS calculation has already been proven by many researchers [37][38][39][40][41][42][43][44][45][46][47][48].…”
Section: Computational Approach and Detailsmentioning
confidence: 98%
“…In this context, it is increasingly important to understand the microscopic nature of SERS using first principle modeling [43]. It is now widely believed that the chemical bonding effects in SERS can be simulated just by considering the local environment of a molecule which is also consistent with the adatom model [26,44].…”
mentioning
confidence: 99%
“…Metal surfaces largely enhance (spontaneous) Raman spectra via the increased fields which exist in the vicinity of a surface plasmon excitation, [29][30][31] although there is also a chemical effect [32][33][34][35] which arises from the metal perturbing the electronic structure of an attached molecule. Classical electrodynamics can account for the former, 36 and TDDFT calculations can be used to describe the latter.…”
Section: Surface Effectsmentioning
confidence: 99%